THE EFFECT OF WORK MOTIVATION ON WORK PERFORMANCE WITH ORGANIZATIONAL COMMITMENT AS MEDIATION AT THE PRIMARY TAX SERVICE OFFICE OF ACEH PROVINCE - Safriani; Jullimursyida; Ibrahim Qamarius; Faisal Matriadi; Marbawi; Mariyudi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to analyze the influence of work motivation on employee performance with organizational commitment as an intervening variable at the Aceh Province Tax Service Office (KPP). The dependent variable of this study is work motivation. The independent variable is employee work performance. The intervening variable is organizational commitment. The population in this study were employees at the Aceh Province Tax Service Office (KPP) totaling 265. The sampling technique used proportionate stratified random sampling and obtained a sample of 170 respondents who were employees at the Aceh Province Tax Service Office (KPP), the research method used was a quantitative method, for the data analysis method using Structural Equation Modeling (SEM). The results of this study indicate that work motivation has a significant effect on organizational commitment, then work motivation and organizational commitment have a significant effect on the work performance of employees of the Aceh Province Tax Service Office (KPP). This study shows that organizational commitment is the most dominant variable influencing the work performance of employees of the Aceh Province Tax Service Office (KPP). In this study, work motivation has a significant influence on employee work performance through organizational commitment as an intervening variable. It can be concluded that organizational commitment functions as a partial mediation between exogenous and endogenous variables.